Association of estimated pulse wave velocity with cardiovascular disease outcomes and all-cause death—a systematic review and meta-analysis - Li, Jian; Gao, Fa; Cao, Fang; Lv, Shan; Hou, Yulong; Guo, Wei; Zhang, Chongheng; Liu, Aidong (Frontiers in Cardiovascular Medicine, 2025)
Background: The estimated pulse wave velocity (ePWV), derived from age and mean blood pressure (MBP) in accordance with the Reference Values of Arterial Stiffness Collaboration, has emerged as a novel alternative indicator for assessing arterial stiffness. This systematic review and meta-analysis aims to assess the correlation of ePWV with the likelihood of adverse cardiovascular (CV) events and all-cause mortality.MethodsStudies published before February 2024 from PubMed, Embase, Cochrane Library, and Web of Science were searched. To ensure the completeness and timeliness of the included literature, a thorough re-search and update of the relevant literature were conducted on April 28, 2025. The data analysis was carried out utilizing STATA (V15.0).ResultsA systematic review and meta-analysis of 20 studies involving 381,303 participants demonstrated that individuals with higher ePWV had significantly increased risks of total CV events (HR = 2.14, 95%CI: 1.70–2.71), CV mortality (HR = 3.64, 95%CI: 2.83–4.68), and all-cause mortality (HR = 1.85, 95%CI: 1.38–2.47). Specifically, for each 1 m/s increase in ePWV, the risks of these outcomes increased by 36%, 41%, and 37%, respectively. Analyses of population types further verified that elevated ePWV was independently associated with increased risks for all outcomes. For total CV events, the HRs were 1.79 (95%CI: 1.45–2.21) in the general population and 3.43 (95%CI: 2.62–4.49) in those with CVD. For CV mortality, the HRs were 4.90 (95%CI: 2.78–8.64) and 3.39 (95%CI: 2.56–4.49), respectively. For all-cause mortality, HRs were 2.28 (95%CI: 1.00–5.21) in the general population and 1.84 (95%CI: 1.20–1.42) in the CVD group. Moreover, each 1 m/s increase in ePWV was associated with a 27% and 54% increase in total CV event risk, a 28% and 54% increase in CV mortality, and a 47% and 30% increase in all-cause mortality in the general and CV populations, respectively.ConclusionThese findings highlight ePWV as a potential predictor of adverse health outcomes, warranting further research to establish reference values and compare with carotid-femoral pulse wave velocity.Systematic Review RegistrationPROSPERO CRD42024536235.